2013
DOI: 10.1155/2013/867389
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Human Herpesvirus 6 as a Trigger of Autoimmune Disease

Abstract: Human herpesvirus 6 (HHV-6) infection is common and has a worldwide distribution. Recently, HHV-6A and HHV-6B have been reclassified into two distinct species based on different biological features (genetic, antigenic, and cell tropism) and disease associations. A role for HHV-6A/B has been proposed in several autoimmune disorders (AD), including multiple sclerosis (MS), autoimmune connective tissue diseases, and Hashimoto's thyroiditis. The focus of this review is to discuss the above-mentioned AD associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…Among viral infections, EBV shows the strongest association, and it was estimated that EBV-induced infectious mononucleosis increases the risk of MS to a similar degree as the strongest genetic risk factor (HLA-DRB1*15:01) [4,[9][10][11]. In addition to EBV, several other viruses have been implicated in MS [12], in particular neurotropic viruses, including human herpes virus-6 (HHV-6) [13], herpes zoster virus [14] and John Cunningham virus (JCV) [15], but also endogenous retroviruses [16]. Based on this evidence, a possible viral etiology of MS has been proposed [9,13,15,17] and continues to stimulate intense research in the field [ 6 7 1 _ T D $ D I F F ] (see Outstanding Questions).…”
Section: Trendsmentioning
confidence: 99%
“…Among viral infections, EBV shows the strongest association, and it was estimated that EBV-induced infectious mononucleosis increases the risk of MS to a similar degree as the strongest genetic risk factor (HLA-DRB1*15:01) [4,[9][10][11]. In addition to EBV, several other viruses have been implicated in MS [12], in particular neurotropic viruses, including human herpes virus-6 (HHV-6) [13], herpes zoster virus [14] and John Cunningham virus (JCV) [15], but also endogenous retroviruses [16]. Based on this evidence, a possible viral etiology of MS has been proposed [9,13,15,17] and continues to stimulate intense research in the field [ 6 7 1 _ T D $ D I F F ] (see Outstanding Questions).…”
Section: Trendsmentioning
confidence: 99%
“…Although originally considered lymphotropic, the in vivo tropism of both viruses is considerably broader, including macrophages, endothelial cells, salivary glands, and brain [5]. HHV-6B is associated with childhood exanthema subitum , whereas HHV-6A is mostly adult-associated, and has been correlated to several chronic autoimmune inflammatory diseases, including AITD [5, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…111114 Recent studies have shown an association between AITD and HHV-6 infection and in vitro HHV-6 virus modulation of micro RNA expression in thyrocytes and T-cell lines. 115118 …”
Section: Immune Mechanisms Of Im-adrsmentioning
confidence: 99%